2020
DOI: 10.1080/14616734.2020.1800769
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood attachment stability and change: a meta-analysis

Abstract: Examining degrees of stability in attachment throughout early childhood is important for understanding developmental pathways and for informing intervention. Updating and building upon all prior meta-analyses, this study aimed to determine levels of stability in all forms of attachment classifications across early childhood. Attachment stability was assessed between three developmental epochs within early childhood: infancy, toddlerhood, and preschool/early school. To ensure data homogeneity, only studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 73 publications
3
27
1
Order By: Relevance
“…To date, no other studies have supported this hypothesis. Given that attachment representations are susceptible to change with time, being less stable in childhood than adulthood ( 7 , 27 ), it is also possible that some children assessed as secure at the time of the study may have been insecurely attached before they developed diabetes. The availability, consistency, and responsiveness of medical professionals, such as the diabetes pediatrician (24-h phone availability) and the availability of care offered by other professionals from the diabetes team (nurses, educators, dietitians, psychologists, child psychiatrists, group and family therapists), could provide a safer environment for the families of children with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no other studies have supported this hypothesis. Given that attachment representations are susceptible to change with time, being less stable in childhood than adulthood ( 7 , 27 ), it is also possible that some children assessed as secure at the time of the study may have been insecurely attached before they developed diabetes. The availability, consistency, and responsiveness of medical professionals, such as the diabetes pediatrician (24-h phone availability) and the availability of care offered by other professionals from the diabetes team (nurses, educators, dietitians, psychologists, child psychiatrists, group and family therapists), could provide a safer environment for the families of children with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…3) Can you see yourself in the future encouraging suitable parents to participate in MERTIL for Parents as a first intervention step? (3) What are the long-term and short-term implications of programs such as MERTIL for Parents ?…”
Section: Methodsmentioning
confidence: 99%
“…These two types of insecure attachments were defined in a clinical context as enmeshed and fearful vulnerable attachment styles respectively (Bifulco, Mahon, Kwon, Moran, & Jacobs, 2003 ). These attachment styles were often stable from early childhood to adulthood, especially for secure attachment, but attachments can also vary over time (Opie et al, 2020 ). A longitudinal study found that early infant attachment were important for emotional regulation later in life (Girme, Jones, Fleck, Simpson, & Overall, 2020 ).…”
Section: The Role Of Adult Vulnerable Attachment For Ptsd and Social Supportmentioning
confidence: 99%